Effect of amyloid‐β (Aβ) immunization on hyperphosphorylated tau: a potential role for glycogen synthase kinase (GSK)‐3β. (June 2015) - Amin, Jay; Paquet, Claire; Baker, Alex; Asuni, Ayodeji A.; Love, Seth; Holmes, Clive; Hugon, Jacques; Nicoll, James A. R.; Boche, Delphine
<x xml:space="preserve">Abstract</x> Aims Active amyloid‐β (Aβ) immunotherapy in Alzheimer's disease (AD) induces removal of Aβ and phosphorylated tau (ptau). Glycogen synthase kinase (GSK)‐3β is a kinase, responsible for phosphorylation of tau, activation of which can be induced by phosphorylated double‐stranded RNA‐dependent protein kinase (pPKR). Using a post‐mortem cohort of immunized AD cases, we investigated the effect of Aβ immunization on GSK‐3β expression and pPKR. Methods We immunostained 11 immunized AD cases and 28 unimmunized AD cases for active, inactive and total GSK‐3β, and for pPKR. Quantification of protein load was performed in the hippocampal region including CA1, subiculum and entorhinal cortex. Results All three areas showed a significant decrease in the three forms of GSK‐3β (P < 0.05) and a nonsignificant trend towards lower pPKR load in the immunized AD cases compared with the unimmunized AD cases. Conclusion The lower GSK‐3β expression generated by Aβ immunotherapy shows evidence of a modification of the signalling pathway induced by GSK‐3β leading to the overall reduction of tau, supporting the contention that in humans, GSK‐3β unifies Aβ and tau‐related neuropathology.